JURIDICAL ANALYSIS OF IMPLEMENTING THE PRESIDENTIAL THRESHOLD IN THE PRESIDENTIAL ELECTION OF INDONESIA - Mubarik Rahmayanti; Irfan Amir (Jurnal Al-Dustur, 2021)
Since issuing the Constitutional Court Decision Number 14/PUU-XI/2013, the general election design must be carried out simultaneously between the election of legislative members and the election of the President and Vice President (Pilpres). Article 6A Paragraph (2) of the 1945 Constitution mandates that pairs of candidates for President and Vice-President are proposed by political parties or coalitions of political parties taking part in the general election prior to implementing the general election. Accordingly, in order to strengthen the presidential system, pairs of candidates proposed in the presidential election are required to meet the "presidential threshold," which essentially limits the rights of political parties in proposing presidential and vice-presidential candidates. This study analyzes the relevance of presidential threshold requirements elections simultaneously. The research method used is normative juridical, using an approach to the application of laws and an analytical approach. This study shows that the application of the presidential threshold that must be met by political parties or a combination of political parties in carrying out the presidential and vice-presidential candidate pairs in the simultaneous general election is less relevant and limits the rights of political parties. In addition, the political party that wins the majority vote has strong dominance to pressure other parties in determining the candidate. Although it does not have high dominance, it still has substantial authority to nominate it.